Konflik Lahan Pemukiman Pada Tanean Lanjheng - Muyassaroh Muyassaroh; Iskandar Dzulkarnain (DIMENSI - Jurnal Sosiologi, 2022)
Conflict in society is something that cannot be separated, where there is a community there is conflict. And conflict will be negative. When one society shakes the synergy of the social system, one of them is fighting or violence. Conflict over land can also lead to violence and fights, because land is one of the most valuable things in people's lives, this can happen anywhere and this condition can happen to the Gritan Hamlet, Tlomar Village, where they are still implementing the tanean lanjheng house structure. The purpose of this study is to find out how to resolve conflicts over residential land on tanean lanjheng. In this study the author uses the theory of social conflict. Conflicts that occur in society do not only show a negative function, but can also have a positive impact. Therefore, conflict can be beneficial for the system concerned, conflict is a form of interaction and its existence should not be denied. The research method used is descriptive qualitative using a case study approach. Informant selection technique using purposive sampling. Data collection techniques using observation, interviews and documents. Data collection techniques using data reduction, data presentation and drawing conclusions. The data validity technique uses source triangulation.